Dental arches dimensions, forms and its association to facial types in a sample of Iraqi adults with skeletal and dental class II-division 1 and class III malocclusion(A cross sectional study) - Hanadi M Al-Taee; Sami K Al-Joubori (College of Dentistry/ University of Baghdad, 2014)
Background: The association between facial types and dental arches forms has considerable implications in orthodontic diagnosis and treatment planning. The aim was to establish the maxillary and mandibular dental arches width and length in skeletal and dental class II division 1 and class III malocclusion groups, find out the most frequent dental arch form and facial type and the association between them and to check the gender differences. Materials and Methods: Frontal and lateral facial photographs and maxillary and mandibular occlussal photographs for 90 iraqi subjects with age 18-25 years old (45 males and 45 females) divided equally into three groups, the 1st group with class II division 1malocclusion (overjet more than 3mm but less than or equal to 6mm), the 2nd group with class II division 1malocclusion (overjet more than 6mm) while the 3rd group with class III malocclusion (edge to edge or reverse overjet).Six linear measurements for each maxillary and mandibular dental cast photographs and two liner measurements for frontal and profile facial photographs was analyzed with (AUTO CAD 2013), which simplified the analyzing process and reduced the time and effort spent on taking measurements directly from the records to facilitate work and to gain more accurate results. Results: All the mean value of dental arches and facial measurements were higher in male than female, the most frequent maxillary and mandibular dental arch form in the three groups was the mid arch form follow by the narrow then the wide arch form except in the mandibular dental arch of the 3rd group it follow by the wide then the narrow arch form.The most frequent facial type in the 1st group is the Mesoprosopic one,followed by the Leptoprosopic then the Euryprosopic face type while in the 2nd and 3rd group the most frequent facial type is the Leptoprosopic, follow by the Mesoprosopic then the Euryprosopic facial type. An association was found between mid arch form and the Mesoprosopic face type in the 1st group, while no clear association was found between dental arch form and facial type in the 2nd and 3rd group for both genders. Conclusions: It was concluded that there was an association between facial type and dental arch form in subject with class II division 1malocclusion (overjet not more than 6mm), while in subject with class II division 1malocclusion (overjet more than 6mm) or with class III malocclusion (edge to edge or reverse overjet) no clear association was found between dental arch form and facial type.